Synthesis and electronic properties of polycyclic aromatic hydrocarbons doped with phosphorus and sulfur. Issue 5 (8th December 2015) - Delaunay, W.; Szűcs, R.; Pascal, S.; Mocanu, A.; Bouit, P.-A.; Nyulászi, L.; Hissler, M.
Abstract : Synthesis and physical properties of polyaromatic hydrocarbons containing phosphole and thiophene rings at the edge. Abstract : In this work, we report on the synthesis of polyaromatic hydrocarbons containing phosphole and thiophene rings at the edge. The ring-closure reactions have been investigated by theoretical calculations. The optical and electrochemical properties and density functional theory calculations showed that the properties depend on the relative position of these five membered rings in the PAH structure.